Episodes From The Life Of Dr Jekyl And Mr Hyde - Bush, Paul (United Kingdom, 2000)
Donation from OSI-Budapest Arts and Culture Program. Duration: 00:05:20 Part of "Made In London" DVD. Thirteen pieces of work represent a small selection of the artists' film and video productions funded through the first five years of the London Artists' Film and Video Awards (LAFVA).